Prevalence and Correlates of Psychological Distress Among HIV Positive Individuals in South Africa: Findings from the 2012 HIV National Household Survey - Ncitakalo, Nolusindiso; Mabaso, Musawenkosi; Maduna, Vincent; Joska, John; Simbayi, Leickness (Journal of Psychology and Psychotherapy Research, 2019)
Psychological distress symptoms like depression and anxiety are potentially dangerous conditions in HIV positive individuals influencing health-seeking behaviour, care and treatment leading to poor health outcomes. This study sought to determine the prevalence of psychological distress symptoms and associated socio-demographic and health-related factors amongst HIV positive individuals. The study used the 2012 data from a nationwide cross-sectional population-based household survey that was conducted using a multi-stage stratified cluster sampling design. Bivariate and multivariate logistic regression analysis were used to identify factors associated with psychological distress among HIV positive individuals. Of 2 536 HIV infected individuals found in the study, 34.5% reported psychological distress symptoms. The prevalence of reported psychological distress symptoms was significantly higher among females (38.2%) than males (28.5%). Increased likelihood of psychological distress among HIV positive males was significantly associated with residing in urban informal areas than urban formal areas [OR=2.5(95% CI: 1.2-5.6), p=0.021], not engaging in vigorous intensity sport [OR=2.1 (95% CI: 1.2-3.8), p=0.009]. The decreased likelihood was significantly associated with being employed [OR=0.6 (95% CI: 0.4-1.0), p=0.066], not having any chronic condition [OR=0.5(95% CI: (0.3-1.0), p=0.037], and low risk drinkers than hazardous drinkers [OR=0.3(95% CI: 0.1-0.9), p=0.036]. Among HIV positive females, increased likelihood of psychological distress was significantly associated with never seeing a health personnel [OR=2.8 (95% CI: 1.2-6.7), p=0.022]. The decreased likelihood was significantly associated with seeing a health personnel more than one year ago than in the past 6 months [OR=0.7 (95% CI: 0.4-1.0), p=0.051], and not having any chronic conditions [OR=0.6 (95% CI: 0.5-0.9), p=0.017]. The findings suggest a need for integrated interventions including those addressing mental health issues which target HIV positive individuals in urban informal areas, the unemployed, hazardous risk drinkers, and those with chronic medical conditions.